Ultrasonic tomography of complex shaped carbon fiber composites; MATEC Web of Conferences; Vol. 48 : Space Engineering - Zhvyrblya V. Yu. Vadim Yurievich; Filippov G. A. German Alekseevich; Sedanova E. P. Elizaveta Pavlovna; Salchak Ya. A. Yana Alekseevna (Modern Technologies and Control Methods in the Aviation and Space Industries, 2016)
Title screen